2014
DOI: 10.1665/034.023.0203
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Feeding Preference ofCornops aquaticum(Orthoptera: Acrididae) onEichhornia crassipesand Crop Plants in Native Area

Abstract: the semiaquatic grasshopper Cornops aquaticum Bruner, which is highly specific of Eichhornia crassipes (Pontederiaceae), constitutes one of the most abundant herbivores in the neotropical wetlands and a possible biological control agent of this weed in south africa. the aims of this study were 1) to assess the performance of each age category of C. aquaticum on crop plants and the host plant E. crassipes; 2) to assess the feeding preference of this grasshopper on crop plants in the presence and absence of E. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In weed biological control, there is often very little data available on a potential agent from the native range. However, in the case of C. aquaticum , several studies have elucidated its feeding ecology in wetlands of Brazil and northern Argentina (e.g., Ferreira & Vasconcellos‐Neto, 2001; Lhano et al, 2005; Capello et al, 2011; Franceschini et al, 2011, 2014; Braga et al, 2014). These studies have shown that this insect is highly specific to P. crassipes for oviposition and feeding, with some feeding, but to a lesser degree, on a few non‐host species.…”
Section: Introductionmentioning
confidence: 99%
“…In weed biological control, there is often very little data available on a potential agent from the native range. However, in the case of C. aquaticum , several studies have elucidated its feeding ecology in wetlands of Brazil and northern Argentina (e.g., Ferreira & Vasconcellos‐Neto, 2001; Lhano et al, 2005; Capello et al, 2011; Franceschini et al, 2011, 2014; Braga et al, 2014). These studies have shown that this insect is highly specific to P. crassipes for oviposition and feeding, with some feeding, but to a lesser degree, on a few non‐host species.…”
Section: Introductionmentioning
confidence: 99%